Food Insecurity May be an Independent Risk Factor Associated With Erectile Dysfunction in the United States: Analysis of the National Health and Nutrition Examination Survey Data. Issue 5 (2nd August 2022) - Wang, Wei; Chen, Jiawei; Peng, Liao; Gao, Xiaoshuai; Lin, Lede; Xiong, Yang; Zhang, Fuxun; Ma, Yucheng; Qin, Feng; Yuan, Jiuhong
Abstract: Introduction: While food insecurity is a global public health problem associated with obesity, diabetes, hypertension and coronary heart disease, literature regarding the relationship between food insecurity and erectile dysfunction (ED) is scarce. Aim: We aimed to determine the associations between food insecurity and ED in the National Health and Nutrition Examination Survey. Methods: Data was extracted from 3, 891 participants (aged ≥ 20 years) with ED in the 2001–2004 National Health and Nutrition Examination Survey. Multivariable logistic regression analysis with sampling weights was conducted to evaluate the associations. Main outcome measure: Food security was assessed utilizing the Household Food Security Module. A single-question self-report from the Massachusetts Male Aging Study was utilized to evaluate ED status. Results: Approximately 10.2% of individuals had food insecurity. Food insecurity was significantly associated with ED after full adjustment (odds ratio [OR] 1.56; 95% confidence interval [95% CI] 1.16–2.09; P = .003). Men with very low food insecurity had 59% higher risks of ED compared with those having high food security (OR 1.59; 95% CI 1.13–2.27; P = .006). Moreover, the associations were stronger in the old people (age ≥ 60) (OR 2.15; 95% CI 1.26–3.66; P = .004). Conclusions: Food insecurity might be associated with higher risks of developing ED.